2014
DOI: 10.1155/2014/814182
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G Polymorphism (rs16375) and Acute Rejection in Liver Transplant Recipients

Abstract: Background. HLA-G molecules exhibit immunomodulatory properties that can delay graft rejection. The 14 bp insertion/deletion polymorphism (INDEL) (rs16375) influences the stability of final HLA-G mRNA and its soluble isoforms. Objective. The present study aimed to investigate the possible association between this polymorphism and the incidence of acute rejection in Iranian liver transplant recipients. Methods. Different genotypes were evaluated by PCR. The patients who had acute rejection within 6 months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Four gene polymorphisms in CTLA-4 CT60 region (dbSNP rs182533364 C/T, rs345031880 T/C, rs3087243 G/A, rs11571319 G/A) were analyzed by the SBT technique, using primers already described in literature (Azarpira et al, 2010;Canossi et al, 2013). Typing was obtained by alignment of the processed sequences with exon 4 sequences of the human CTLA-4 gene reference from the Genebank.…”
Section: Editorial Policies and Ethical Considerationsmentioning
confidence: 99%
“…Four gene polymorphisms in CTLA-4 CT60 region (dbSNP rs182533364 C/T, rs345031880 T/C, rs3087243 G/A, rs11571319 G/A) were analyzed by the SBT technique, using primers already described in literature (Azarpira et al, 2010;Canossi et al, 2013). Typing was obtained by alignment of the processed sequences with exon 4 sequences of the human CTLA-4 gene reference from the Genebank.…”
Section: Editorial Policies and Ethical Considerationsmentioning
confidence: 99%
“…This molecule has local immunomodulatory properties, due to its limited polymorphism, contributing to the survival of allogeneic liver transplants. HLA-G1 to G4 are membrane-bound molecules while HLA-G5 to G7 are soluble molecules (sHLA-G) [ 87 , 88 ]. HLA-G was previously identified as a naturally occurring tolerance-inducing molecule.…”
Section: Adaptive Immunity On Graft Rejectionmentioning
confidence: 99%
“…Since its discovery, the crucial role of the non-classical HLA-G molecule in pregnancy success has been demonstrated (22,23). Various studies have reported that HLA-G molecules are responsible for maintaining the immune-regulated and tolerogenic environment during pregnancy (8,24,25). Indeed, these molecules are predominately expressed on extra villous cytotrophoblasts at the fetal-maternal interface during pregnancy (26).…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%